The first single-cell sequencing of Plasmodiophora brassicae reveals genetic diversity and clonal dynamics - Sedaghatkish, Afsaneh; Kunz, Meik; Gossen, Bruce D.; McDonald, Mary Ruth (Frontiers in Microbiology, 2025)
Clubroot, caused by the obligate Chromist pathogen Plasmodiophora brassicae, is an important disease of brassica crops but little is known about its reproductive biology. We enzymatically removed cell walls from dormant spores to generate protoplasts, enabling the first single-cell sequencing of P. brassicae with DNA free from host and soil microbial contamination. Analysis of 4,000 protoplasts from a single root showed moderate genetic diversity, with 2–5 distinct genotypes. A more detailed analysis of the 500 cells indicated the presence of seven distinct genotypes, accounting for rare haplotypes. This level of genetic diversity in a single root supports other indications that there is a high genetic diversity in field populations of P. brassicae. These results support the hypothesis that balancing selection maintains multiple genotypes within the pathogen population. This level of diversity complicates the use of single-gene resistance sources for clubroot management and explains the short durability of clubroot resistance. The predominance of distinct genotypes in a single root is a strong indication that reproduction of P. brassicae is predominantly clonal. This is the first whole genome DNA sequencing of a single-cell of a plant pathogen.